Employer attitudes towards general health checks and HIV testing in the workplace. (March 2018) - Blake, H.; Banerjee, A.; Evans, C.
Abstract: Objective: There is a need to increase HIV testing rates in the UK. One approach is to increase access to testing through general health checks (GHCs) in the workplace. However, it is unclear whether GHCs are routinely offered by organisations, and employer perceptions of HIV testing are largely unknown. Study design: Online survey to assess attitudes towards and provision of general health checks and HIV testing in the workplace. Methods: Ninety-eight employers from 25 job sectors completed an online survey. Employers were 61 small and medium-sized enterprises (SME), 37 large organisations; 86% employing mobile workers, 77.6% employing migrant workers and 51.7% of employees were male workers. Items included employer attitudes around workplace health, GHC provision, content and delivery and attitudes towards workplace HIV testing including perceived benefits and barriers to HIV testing. Results: Only one company offered opt-in workplace HIV testing. Seventy-eight companies (80%) did not provide any form of workplace GHC for employees. Decisions about health check provisions were not commonly informed by staff consultation (n = 6) or national guidelines (n = 4). Overall, 100% of companies (n = 98) reported at least one benefit of HIV testing and 68 (69%) believed that HIV testing should be offered in the workplace. Perceived barriers to HIV testing in the workplace were: [a] not having enough knowledge about HIV and testing; [b] not having trained staff to undertake HIV testing; and, [c] not knowing how to access HIV testing kits. Fifty-six companies (57.14%) would consider HIV testing as a future provision at their organisation. Sixty-seven companies (68.37%) would like further guidance on workplace HIV testing. Conclusions: Few employers offer general health testing for employees, and opt-in HIV testing is exceptionally rare, despite positive attitudes towards it. There is a need to provide evidence-based guidance and support for employers around HIV testing in the workplace. Highlights: Opt-in HIV testing is rarely offered in the workplace setting. Employers are positive towards workplace general health testing with opt-in HIV tests. Organisational barriers include lack of HIV-related knowledge and access to testing resources. Employer guidance and support is required around workplace HIV testing. Normalising HIV testing at work may increase access to testing in at-risk groups.